A análise das contradições pragmáticas sob um olhar linguístico-jurídico - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Establishing the role of the judiciary in the event of Brazilian Family Law is one of the commitments of the magistrates in family conflicts. In order to build, new knowledge renewals and experiences based on a multidisciplinary proposal possible. For reason, Pragmatic, and Law will be present in this work, specifically the scene forensics Food Action Execution (004/111) of the Probate and Family Court of the District of Bage. Thus, this Action Execution Foods, contribute to an analysis from the perspective of linguistic competence of legal agents involved in this balance pragmatic communication context. Thus, the analysis will start from the pragmatic understanding of the contradictions, implying both the controversies, the stability and regularity of the pragmatic appeals ethos, pathos, and logos.
Keywords: Direito; Pragmática; Ação de alimentos; Contradição pragmática; Balança pragmática; Law; Pragmatic; Pragmatic contradiction; Pragmatic balance; CNPQ::LINGUISTICA, LETRAS E ARTES